The Great Witness of Little Armtan - Avagyan, Artsrun (Bulletin of Yerevan University B: Philology, 2023)
The article “The Great Witness of Little Armtan” comprehensively examines the initial period of the life of Hakob Mndzuri, a classic of Armenian literature of the Diaspora, based on the press of the previous century, biographical materials and works of the writer, which are presented for the first time. A review of the period of his life, spent in his native village, then in Istanbul and again in his native land (1886-1914) has been made. The article is about the Yerznka Province of Western Armenia, a number of its villages, and especially Armtan and its inhabitants, about life, national customs, human relations, as well as writer’s career. The period of his life before the First World War has been also presented. The article focuses on the eventful life of young Hakob, which gradually formed the image of the future great writer, who lived his life in a country that no longer exists, where peaceful people saw the meaning of life in creativity and work. The article contains rich material related to the life of Western Armenians, revealing the ideological and artistic merits of the works of Hakob Mndzuri.